Analysis of Sharia Compliance in the Wakalah Contract for Zakat Payment on Tokopedia: تحليل مدى توافق الشريعة في تطبيق عقد الوكالة على قضية دفع الزكاة عبر توكوبيدي - Rosyadi, Fazlur Rahman; Arif, Zainal; Rosyadi , Zidan Nayyiv (Indonesian Journal of Islamic Economic Law, 2025)
The objective of this study is to analyse the Sharia compliance of the wakalah contract applied in zakat payments via Tokopedia, in order to ascertain the validity of transactions between the muzakki and Tokopedia as an intermediary with zakat administrators (amil zakat). The study employs content analysis to understand Sharia compliance in the wakalah contract for zakat payments via Tokopedia. It adopts a deductive approach, testing Sharia compliance theory within this specific context. The data collection process involves a document study, wherein relevant fuqaha's opinions and related scholarly articles are analysed. Thematic analysis is then employed to identify patterns or specific meanings relevant to the research focus. The findings indicate that zakat payments via Tokopedia using a wakalah contract fulfil the essential pillars and conditions of the wakalah contract, thereby rendering them valid under Islamic law. However, a shortcoming is identified in the form of delays in updating zakat distribution reports. The novelty of this study lies in its comprehensive analysis of the implementation of the wakalah contract in digital zakat payments via Tokopedia, along with recommendations for enhancing the transparency of zakat distribution reporting on a regular basis.